The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.jacc.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The ARBITER 6-HALTS Trial (Arterial Biology for the Investigation of the Treatment Effects of Reducing Cholesterol 6–HDL and LDL Treatment Strategies in Atherosclerosis)

Abstract: Niacin induces regression of CIMT and is superior to ezetimibe for patients taking statins. (Comparative Study of the Effect of Ezetimibe Versus Extended-Release Niacin on Atherosclerosis; NCT00397657).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
1
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(135 citation statements)
references
References 14 publications
3
124
1
7
Order By: Relevance
“…Ускорение АТ в ответ на ристомицин у больных обусловлено усилением выработки в эндотелии сосу-дов фактора Виллебранда [15]. Короткая длитель-ность АТ с сочетаниями индукторов и большое число агрегатов тромбоцитов в крови пациентов до и после венозной окклюзии указывали на выраженное осла-бление сосудистого контроля над активностью тром-боцитов у пациентов в условиях, близких к реальным.…”
Section: Discussionunclassified
“…Ускорение АТ в ответ на ристомицин у больных обусловлено усилением выработки в эндотелии сосу-дов фактора Виллебранда [15]. Короткая длитель-ность АТ с сочетаниями индукторов и большое число агрегатов тромбоцитов в крови пациентов до и после венозной окклюзии указывали на выраженное осла-бление сосудистого контроля над активностью тром-боцитов у пациентов в условиях, близких к реальным.…”
Section: Discussionunclassified
“…58 Despite the negative findings of recent large-scale trials, several earlier studies -though at smaller scales -have reported an opposite finding. 18,33,[59][60][61][62][63][64] A recent meta-analysis also favored the benefits of niacin either as monotherapy or as an adjunct to statins in reducing CVD events. 64 It is also worth noting that both AIM-HIGH and HPS2-THRIVE studies were secondary prevention trials in subjects receiving optimal statin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The ARBITER 6-HALTS (Arterial Biology for the Investigation of the Treatment Effects of Reducing Cholesterol 6-HDL and LDL Treatment Strategies in Atherosclerosis) trial showed that niacin not only favorably modified lipid profiles, but also reduced plaque formation in carotid and coronary arteries. 89 Unfortunately, the large outcome trial AIM-HIGH (Atherothrombosis Intervention in Metabolic Syndrome with Low HDL/High Triglycerides), supported by the National Institutes of Health, was stopped after a little more than 3000 patients had been recruited, because of futility. 9 The trial has been criticized for its small sample size and the fact that the dose of simvastatin (which was used as background therapy to control LDL-C) had been adapted to the LDL levels achieved with either placebo or niacin.…”
Section: Hdl As a Therapeutic Targetmentioning
confidence: 99%